(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article, improving the content of the processes of increasing the level of methodological training of future teachers of computer science, the search for information, processing, revising their point of view in the context of the progress of Science and changing social practice, choosing innovative forms and methods of work.